Association of over-the-counter mouthwash use with markers of nitric oxide metabolism, inflammation, and endothelial function—a cross-sectional study - Guo, Kai; Joshipura, Kaumudi; Ricart, Karina; Patel, Rakesh P.; Gower, Barbara A.; Andriankaja, Oelisoa Mireille; Morou-Bermudez, Evangelia (Frontiers in Oral Health, 2025)
IntroductionRegular use of mouthwash can disrupt nitrate reduction by oral bacteria and may affect systemic nitric oxide (NO) levels, which are important for inflammation and endothelial function. We aim to assess the association between over-the-counter (OTC) mouthwash use and nitrate/nitrite, markers of inflammation (IL-6, TNF-α, CRP) and endothelial function (sICAM-1, sVCAM-1) in serum and saliva, and to assess the relationship between nitrate/nitrite levels and these biomarkers, as well as how OTC mouthwash modulated this relationship. We hypothesize that nitrates/nitrites are associated with these biomarkers, and that their associations would vary with the frequency of mouthwash use.MethodOur cross-sectional study used data and specimen from the baseline of the San Juan Overweight Adult Longitudinal Study (SOALS). Robust Gamma regression with log-link function, Spearman correlations and partial correlations adjusted for covariates were used for the analysis.ResultsUsing OTC mouthwash twice a day or more was significantly associated with lower serum nitrite levels compared to less frequent use (β = −0.357, 95% CI: −0.650, −0.064), but not with other markers of inflammation and endothelial function. Mouthwash use differentially impacted the relationship between nitrate/nitrite and TNF-α, sICAM-1 and sVCAM-1. Specifically, in the participants who used mouthwash less than twice a day or no use, TNF-α (β = −0.35, 95% CI: −0.52, −0.18), and sICAM-1 (β = −0.21, 95% CI: −0.32, −0.09) were negatively associated with serum nitrite. In the participants who used mouthwash twice a day or more use, TNF-α was positively associated with serum nitrate (β = 3.36, 95% CI: 2.07, 4.65), salivary nitrite (β = 1.04, 95% CI: 0.39, 1.69) and salivary nitrate (β = 0.48, 95% CI: 0.25, 0.71); sICAM-1 was positively associated with serum nitrate (β = 1.58, 95% CI: 0.86, 2.29). In both subgroups of mouthwash users, sVCAM-1 was positively correlated with serum nitrate and salivary nitrate. In addition, sVCAM-1 was positively correlated with serum nitrite in participants who used mouthwash frequently (ρ_S = 0.18, p = 0.045).DiscussionRegular use of OTC mouthwash was associated with systemic nitric oxide. This raises concerns about its potential effects on the levels of inflammatory and endothelial biomarkers associated with cardiometabolic diseases.